Praktek Kepengasuhan Anak Dalam Rumah Tangga Berdasarkan Tingkat Pendidikan Istri di Desa Ngronggot Kecamatan Ngronggot Kabupaten Nganjuk - Muzdalifah, Ela; Qurotul Aini, Siti Maryam; Ma’sum, Toha (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2025)
An intelligent and capable mother is closely related to the knowledge and skills she acquires through the educational process. Education plays a significant role in shaping individual and family life and constitutes a lifelong necessity. For mothers, education is particularly important in supporting self-development and effective child-rearing practices, which ultimately influence family well-being. This study aims to examine child-rearing practices in Ngronggot Village, Ngronggot District, Nganjuk Regency, based on the wife’s level of education. In addition, it analyzes the supporting and inhibiting factors of parenting practices and the impact of the wife’s educational level on child upbringing. This research employs a qualitative approach using observation and interview techniques for data collection. The findings reveal that mothers with elementary and junior high school education tend to apply permissive parenting styles, whereas those with senior high school, undergraduate, and Islamic boarding school education predominantly adopt democratic parenting styles. Mothers with lower educational backgrounds generally have limited understanding of children’s rights as stipulated in the Child Protection Law, while mothers with higher education demonstrate better awareness of the fulfillment of children’s rights. Supporting factors in child-rearing practices include effective communication between husband and wife, family support, the social environment, educational institutions such as Qur’anic learning centers (TPQ), and parents’ educational levels. Conversely, the main inhibiting factor is parents’ limited knowledge. The impact of the wife’s educational level on child-rearing practices is reflected in children’s growth, personality development, and overall character formation.